2016
DOI: 10.1039/c6tc00960c
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic double-tartaric bridging mono-lanthanide substituted phosphotungstates with photochromic and switchable luminescence properties

Abstract: A series of inorganic–organic hybrid multifunctional crystalline materials constructed using double-tartaric bridging mono-lanthanide substituted phosphotungstates display reversible photochromic, switchable luminescence, and magnetic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 71 publications
12
58
0
Order By: Relevance
“…Low temperature field dependent magnetization was measured for all complexes. Experimental values were found the be significantly lower than the theoretical values for M J =±6 and M J =±15/2 ground states (9 and 10 μ B , respectively), and non‐saturation of magnetization at high field suggests the presence of appreciable magnetic anisotropy and/or of low‐lying excited states (Figure ii) . This conclusion is supported by non‐superposition of the M vs. B / T plots at higher field (see Figure S3)…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Low temperature field dependent magnetization was measured for all complexes. Experimental values were found the be significantly lower than the theoretical values for M J =±6 and M J =±15/2 ground states (9 and 10 μ B , respectively), and non‐saturation of magnetization at high field suggests the presence of appreciable magnetic anisotropy and/or of low‐lying excited states (Figure ii) . This conclusion is supported by non‐superposition of the M vs. B / T plots at higher field (see Figure S3)…”
Section: Resultsmentioning
confidence: 83%
“…The values are, however,w ithin the range previously found for mononuclear Dy III and Tb III complexes. [18] This conclusion is supported by non-superposition of the M vs. B/T plots at higherfield( see Figure S3). The more pronounced dropa tl ow temperaturei sl ikely due to magnetic anisotropy.L ow temperature field dependent magnetization was measured for all complexes.…”
Section: Syntheses and Structural Propertiesmentioning
confidence: 79%
“…Both is further witnessed by the linear increase of the M vs. B curve at higher magnetic field without indication of saturation in the accessible field range. [20,33]…”
Section: Magnetic Susceptibility and Magnetizationmentioning
confidence: 99%
“…4,5 Most of these compounds are based on organic ligands, [6][7][8] allowing a finetuning of the dynamic response through chemical modification of the organic moieties, 9 and can find applications as spin valves and qubits. 8,10 The inorganic analogues, i.e., mononuclear SIMs in which the organic ligands have been replaced by inorganic ones, have also been described using different types of lacunary polyoxometalates (LPOMs), [11][12][13][14][15] resulting in more robust systems with applications in quantum computation; 16,17 this is a consequence of the magnetic insulation from the other neighbouring magnetic molecules of the crystal lattice caused by the inorganic moieties. 18,19 On the other hand, theoretical studies have shown that heteroleptic coordination compounds formed by anionic and neutral ligands favour the SMM behaviour in Dy III complexes compared to homoleptic systems.…”
mentioning
confidence: 99%
“…However, all the attempts in this direction have been unsuccessful, producing dinuclear and polynuclear systems. [27][28][29][30][31] Herein we present the first isostructural family of mononuclear hybrid organic-inorganic lanthanoid complexes that present SMM behavior, The combination of the neutral phenanthroline ligand and the anionic inorganic lacunary Keggin POM ligand under hydrothermal synthesis at 160 1C after 48 h yields a molecular heteroleptic complex, LM 4 -1-Ln. Under this experimental condition, the pH becomes more acidic, due to the deprotonation of the inorganic ligand.…”
mentioning
confidence: 99%